Measurements of downburst wind loading acting on an overhead transmission line in Northern Germany. (2017) - Stengel, Dominik; Thiele, Klaus
Abstract: Along an overhead transmission line in Northern Germany, a unique instrumentation of anemometers and force measurements is installed. Details of this test line with wind measurements along a horizontal axis are given. A recent event of a presumable downburst wind event is analyzed by means of available data and precedent works on thunderstorm analysis. The measured response of the conductors at the suspension tower is investigated and compared with time domain simulation of a finite element model.